2016
DOI: 10.3201/eid2206.160064
|View full text |Cite
|
Sign up to set email alerts
|

MERS-CoV Antibodies in Humans, Africa, 2013–2014

Abstract: Dromedaries in Africa and elsewhere carry the Middle East respiratory syndrome coronavirus (MERS-CoV). To search for evidence of autochthonous MERS-CoV infection in humans, we tested archived serum from livestock handlers in Kenya for MERS-CoV antibodies. Serologic evidence of infection was confirmed for 2 persons sampled in 2013 and 2014.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
59
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 14 publications
11
59
0
Order By: Relevance
“…Extension of serosurveys among the human population would help in furthering understanding of the extent of levels of MERS-CoV infection in Africa. In one study use of ELISA, IFA and ppNT showed that there was evidence for unrecorded cases of human MERS-CoV in Kenya, similar to previous reports in KSA (Liljander et al, 2016;Müller et al, 2015).…”
Section: Camelssupporting
confidence: 77%
“…Extension of serosurveys among the human population would help in furthering understanding of the extent of levels of MERS-CoV infection in Africa. In one study use of ELISA, IFA and ppNT showed that there was evidence for unrecorded cases of human MERS-CoV in Kenya, similar to previous reports in KSA (Liljander et al, 2016;Müller et al, 2015).…”
Section: Camelssupporting
confidence: 77%
“…17 A study of humans in Kenya detected MERS-CoV neutralizing antibodies in persons living in rural areas, although no human MERS cases have been detected yet. 18 The primary source of human MERS-CoV infections remains unknown. There are no definitive data on the epidemiologic link between human MERS-CoV infections and bats.…”
Section: Source Of Primary Human Middle East Respiratory Syndrome Cormentioning
confidence: 99%
“…Similarly, a study from Qatar showed that 0.21% of the general population were seropositive by ELISA screening of 4719 blood donors however the presence of nAbs was only confirmed in one blood donor (0.02%) [29]. Interestingly, despite the high prevalence of MERS-CoV in camels from different countries such as Kenya, Nigeria, Egypt and Pakistan, confirmed evidence of MERS cases among humans is very limited in these countries except for two seropositive camel handlers in Kenya [10][11][12][13][14]30]. Such data clearly suggest that unknown asymptomatic and subclinical MERS infections or even unrecognized cases might in fact exist in the general population and could represent an underappreciated source of human-to-human transmission.…”
Section: Introductionmentioning
confidence: 99%